Virtual reality simulation of robotic transsphenoidal brain tumor resection: Evaluating dynamic motion scaling in a master‐slave system - Heredia‐Pérez, Saúl A.; Harada, Kanako; Padilla‐Castañeda, Miguel A.; Marques‐Marinho, Murilo; Márquez‐Flores, Jorge A.; Mitsuishi, Mamoru (The international journal of medical robotics + computer assisted surgery, 2019)
Background Integrating simulators with robotic surgical procedures could assist in designing and testing of novel robotic control algorithms and further enhance patient‐specific pre‐operative planning and training for robotic surgeries. Methods A virtual reality simulator, developed to perform the transsphenoidal resection of pituitary gland tumours, tested the usability of robotic interfaces and control algorithms. It used position‐based dynamics to allow soft‐tissue deformation and resection with haptic feedback; dynamic motion scaling control was also incorporated into the simulator. Results Neurosurgeons and residents performed the surgery under constant and dynamic motion scaling conditions (CMS vs DMS). DMS increased dexterity and reduced the risk of damage to healthy brain tissue. Post‐experimental questionnaires indicated that the system was well‐evaluated by experts. Conclusion The simulator was intuitively and realistically operated. It increased the safety and accuracy of the procedure without affecting intervention time. Future research can investigate incorporating this simulation into a real micro‐surgical robotic system.